2021
DOI: 10.1177/01655515211015135
|View full text |Cite
|
Sign up to set email alerts
|

Open access editorial policies of SciELO health sciences journals

Abstract: SciELO promotes open access and cooperative publication of scholarly journals, based mainly in Latin America, the Caribbean, Spain and Portugal. SciELO was created to offer solutions to increase the visibility of participating journals and facilitate free access to their full texts. This work aims to analyse the open access editorial policies implemented by the health sciences journals of the SciELO network (411 journals at the time of this study) in terms of authors’ rights, copyright issues, self-archiving p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…29 Findings from this study more strongly resemble trends in European journals than the findings on SciELO journals in Latin America and the Caribbean, where it was found that 89 percent of such open access journals required copyright transfer. 30 An important difference, however, is that our study recorded a much higher instance of the copyright status for authors as unknown-22 percent as compared to a negligible amount in the Morrison et al study.…”
Section: Copyright Retentioncontrasting
confidence: 74%
“…29 Findings from this study more strongly resemble trends in European journals than the findings on SciELO journals in Latin America and the Caribbean, where it was found that 89 percent of such open access journals required copyright transfer. 30 An important difference, however, is that our study recorded a much higher instance of the copyright status for authors as unknown-22 percent as compared to a negligible amount in the Morrison et al study.…”
Section: Copyright Retentioncontrasting
confidence: 74%
“…The dataset used in this work results from merging four distinct datasets that share a common set of documents. These datasets correspond to annotated versions of the 1000 clinical cases making up the Spanish Clinical Case Corpus [ 77 ], a collection of clinical case reports obtained from Spanish medical publications [ 78 ], encompassing a total of 16 504 sentences with an average of 16.5 sentences per clinical case. Each of these documents was verified to contain the same text.…”
Section: Methodsmentioning
confidence: 99%